2018
DOI: 10.1038/s41586-018-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

Structure of photosynthetic LH1–RC supercomplex at 1.9 Å resolution

Abstract: Light-harvesting complex 1 (LH1) and the reaction centre (RC) form a membrane-protein supercomplex that performs the primary reactions of photosynthesis in purple photosynthetic bacteria. The structure of the LH1-RC complex can provide information on the arrangement of protein subunits and cofactors; however, so far it has been resolved only at a relatively low resolution. Here we report the crystal structure of the calcium-ion-bound LH1-RC supercomplex of Thermochromatium tepidum at a resolution of 1.9 Å. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
213
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(224 citation statements)
references
References 33 publications
10
213
1
Order By: Relevance
“…To cope with the various light environments where different photosynthetic organisms inhabit, different types and numbers of light‐harvesting antenna proteins are attached to the PSII core to enhance the light‐harvesting and energy‐quenching capacities . The pigments involved in energy harvesting are bacteriochlorophylls in anoxygenic photosynthetic bacteria , and mainly chlorophylls (Chl) a/b and various carotenoids in oxygenic photosynthetic organisms .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To cope with the various light environments where different photosynthetic organisms inhabit, different types and numbers of light‐harvesting antenna proteins are attached to the PSII core to enhance the light‐harvesting and energy‐quenching capacities . The pigments involved in energy harvesting are bacteriochlorophylls in anoxygenic photosynthetic bacteria , and mainly chlorophylls (Chl) a/b and various carotenoids in oxygenic photosynthetic organisms .…”
Section: Introductionmentioning
confidence: 99%
“…This is another important feature of FCPs, since diatoms experience a more dynamic, fluctuating light environment in water due to the continuous flow and mixing of water layers, which would require a more robust system to protect diatoms from photodamage. The outstanding ability of FCPs in absorbing blue‐green light and in dissipating excess energy may constitute one of the major reasons for diatoms to survive successfully in the aquatic environment .…”
Section: Introductionmentioning
confidence: 99%
“…Transmembrane helix prediction on WPS-2 L and M subunits was computed using the TMHMM Server, v. 2.0 (http://www.cbs.dtu.dk/services/TMHMM/) 34 1.0 (http://dgpred.cbr.su.se/) 35 . Structural homology models were carried out with SWISS-MODEL server (https://swissmodel.expasy.org/) 36 using the 1.9 Å crystal structure of the gammaproteobacterium Thermochromatium tepidum as template 14 (PDB ID: 5y5s). The WPS-2 L and M subunits annotated as Ga0175859_11240458 and Ga0175859_11402733 respectively were used for the structural reconstruction.…”
Section: Reaction Center Evolution Analysesmentioning
confidence: 99%
“…These have traditionally been subdivided into two types, the L and M found in the reaction centers of phototrophic Proteobacteria (PbRC) and the L and M found in those of the phototrophic Chloroflexi (CfRC), with each set making separate monophyletic clades 12,13 . Therefore, substantial differences exist between the PbRC and the CfRC not only at the level of photochemistry, but also at the level of sequence identity of the core subunits, pigment and subunit composition 14,15 . Phototrophic Gemmatimonadetes, on the other hand, encode Proteobacteia-like reaction centers, as Zeng et al 10 demonstrated that this group obtained phototrophy via horizontal gene transfer of an entire photosynthesis gene cluster from a gammaproteobacterium.…”
Section: Introductionmentioning
confidence: 99%
“…A [9], which is among the highest resolution for such a large, multi-subunit membrane-protein complex [15].…”
Section: Introductionmentioning
confidence: 99%